Supramolecular Design of Unsymmetric Reverse Bolaamphiphiles for Cell‐Sensitive Hydrogel Degradation and Drug Release. Issue 11 (30th January 2020) - Chakroun, Rami W.; Sneider, Alexandra; Anderson, Caleb F.; Wang, Feihu; Wu, Pei‐Hsun; Wirtz, Denis; Cui, Honggang
Abstract: Self‐assembly of peptide‐based building units into supramolecular nanostructures creates an important class of biomaterials with robust mechanical properties and improved resistance to premature degradation. Yet, upon aggregation, substrate–enzyme interactions are often compromised because of the limited access of macromolecular proteins to the peptide substrate, leading to either a reduction or loss of responsiveness to biomolecular cues. Reported here is the supramolecular design of unsymmetric reverse bolaamphiphiles (RBA) capable of exposing a matrix metalloproteinase (MMP) substrate on the surface of their filamentous assemblies. Upon addition of MMP‐2, these filaments rapidly break into fragments prior to reassembling into spherical micelles. Using 3D cell culture, it is shown that drug release is commensurate with cell density, revealing more effective cell killing when more cancer cells are present. This design platform could serve as a cell‐responsive therapeutic depot for local chemotherapy. Abstract : Drug release : A reverse bolaamphiphile with a chemotherapeutic agent and an MMP‐2 substrate was shown to self‐assemble into a cell‐responsive supramolecular filament hydrogel. Cancer‐expressed MMP‐2 triggered hydrogel degradation through filament fragmentation, eventually releasing therapeutics against cancer cells.